Pemberdayaan dan Digitalisasi untuk Meningkatkan Penjualan Online di Kelurahan Graha Indah - Maryatin, Maryatin; Putri, Kartika Priandita Maharani; Rauf, Achmady (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2026)
Digital transformation has opened up significant opportunities for business operators to enhance their competitiveness and broaden their market reach through the utilization of online sales platforms; however, in Graha Indah Village, Micro, Small, and Medium Enterprises (MSMEs) still face various challenges, such as limited understanding of digital technology, restricted access to digital platforms, and insufficient capacity to implement effective digital marketing strategies, which is why this community empowerment initiative aims to empower MSMEs in Graha Indah Village through education and digital mentoring to enhance their online sales capabilities. The method employed in this activity involves several stages, including identifying the issues faced by MSMEs, conducting intensive training sessions that cover the use of market places, social media and other supporting applications, providing direct mentoring in the application of digital marketing strategies, and evaluating the success of the program based on specific indicators. The results indicate that 85% of the participants have successfully utilized digital platforms to market their products with 60% reporting an increase in sales after applying the strategies taught during the training, and the activity has also succeeded in forming a digital community among MSMEs that facilitates information sharing, collaboration, and future business development. These outcomes demonstrate that a digital empowerment approach can have a significant positive impact on enhancing the capacity of MSMEs at the local level while simultaneously creating a more autonomous and sustainable economic ecosystem, thereby suggesting that this empowerment program could serve as a viable model for supporting digital-based economic transformation in other communities.